HNF4α contributes to hepatic CAR dysfunction in polymicrobial sepsis - Van Dender, Céline; Timmermans, Steven; Roes, Maxime; Hellemans, Madeleine; Moens, Elise; Nuyttens, Louise; Claes, Maarten; Roman, Bart; De Bosscher, Karolien; Vandewalle, Jolien; Libert, Claude (Frontiers in Immunology, 2025)
The constitutive androstane receptor (CAR), encoded by the Nr1i3 gene, is a nuclear receptor mainly expressed in the liver, where it regulates (xenobiotic) drug and bile acid metabolism, bilirubin clearance and energy homeostasis. CAR has emerged as a promising therapeutic target for diabetes, fatty liver disease and alcoholic liver disease, but it has barely been investigated in the context of sepsis. Since alterations in drug metabolism have been observed in sepsis patients, who may also exhibit increased serum bilirubin and bile acid levels, we hypothesize that CAR function may be impaired during sepsis. Here, we demonstrate that CAR loses its function in the liver during sepsis, as evidenced by a diminished response to its agonist TCPOBOP. We show that Nr1i3 mRNA transcription is reduced, mediated by decreased HNF4α binding to the Nr1i3 promoter and by downregulation of Ppara expression. Additionally, we show that CAR DNA binding is impaired, and we propose that HNF4α may regulate chromatin accessibility of CAR binding sites in sepsis. CAR loss-of-function further causes the downregulation of genes involved in monocarboxylic acid, fatty acid, and xenobiotic metabolism, but induces a hepatic acute phase response, which is beneficial for liver regeneration. However, CAR inhibition with CINPA1 increases sepsis lethality, associated with the further downregulation of these metabolic genes, increased upregulation of the acute phase response, but persistent downregulation of proliferation markers in the liver. Altogether, our study highlights the importance of CAR in sepsis with respect to hepatic metabolism, liver regeneration and survival. Nevertheless, CAR is unlikely to serve as a viable therapeutic target in sepsis, given its rapid downregulation and the lack of a survival benefit from TCPOBOP treatment. Instead, targeting upstream regulators such as HNF4α may represent a more effective approach.